An overwhelming pulmonary fungus ball in a systemic lupus erythematosus patient - Kocakoc, E; Ozgocmen, S; Kiris, A; Ozcakar, L; Boztosun, Y; Yildirim, N (Dr Dietrich Steinkopff Verlag, 2003)
Impaired host immunity has been regarded as a predisposing factor in postprimary tuberculosis in adults. Patients with systemic lupus erythematosus (SLE) are usually exposed to high doses of corticosteroids and eventually develop defective cellular immunity that increases the risk for active tuberculosis. SLE-associated pulmonary tuberculosis tends to have a higher incidence of miliary, far-advanced pulmonary disease and therefore establishing the diagnosis can easily be delayed due to generalized, non-specific clinical symptoms such as fever, malaise and weight loss which are also commonly observed in lupus patients. However, cavitary tuberculosis is very rare in patients with SLE. To the best of our knowledge, fungus ball formation in the tuberculosis cavity in a patient with SLE, has not been previously reported. Thus, we present a case of SLE who was found to have a fungus ball within a preexisting tuberculosis cavity. The diagnosis was resolved by computerized tomography of the chest and was confirmed with histopathological examination.
Keywords: fungus ball; tuberculosis; systemic lupus erythematosus; corticosteroid treatment; computed tomography